Low Adverse Event Rates But High Emergency Department Utilization in Chest Pain Patients Treated in an Emergency Department Observation Unit. Issue 1 (March 2017) - Napoli, Anthony M.; Baird, Janette; Tran, Steven; Wang, Jing
Abstract : Objectives: Nearly 40% of all previously admitted chest pain patients re-present to the emergency department (ED) within 1 year regardless of stress testing, and nearly 5% of patients return with a major adverse cardiac event (MACE). The primary objective of this study was to determine the prevalence of return visits to the ED among patients previously admitted to an ED chest pain observation unit (CPU). We also identified the patient characteristics and health risk factors associated with these return ED visits. Methods: This was a prospective cohort study of patients admitted to a CPU in a large-volume academic urban ED who were subsequently followed over a period of 1 year. Inclusion criteria were age ≥18 years old, American Heart Association low-to-intermediate assessed risk, electrocardiogram nondiagnostic for acute coronary syndrome (ACS), and a negative initial troponin I. Excluded patients were those age >75 years with a history of coronary artery disease. Patients were followed throughout their observation unit stay and then subsequently for 1 year. On all repeat ED evaluations, standardized chart abstractions forms were used, charts were reviewed by 2 trained abstractors blinded to the study hypothesis, and a random sample of charts was examined for interrater reliability. Return visits were categorized as MACE, cardiac non-MACE, or noncardiac based on a priori criteria. Social security death index searches were performed on all patients. Univariate and multivariate ordinal logistic regressions were conducted to determine demographics, medical procedures, and comorbid conditions that predicted return visits to the ED. Results: A total of 2139 patients were enrolled over 17 months. The median age was 52 years, 55% were female. Forty-four patients (2.1%) had ACS on index visit. A total of 36.2% of CPU patients returned to the ED within 1 year vs. 5.4% of all ED patients ( P < 0.01). However, the overall incidence of MACE at 1 year in all patients and in those without an index visit diagnosis of ACS was 0.5% (95% confidence interval [CI], 0.4%–06%) and 0.4% (95% CI, 0.2%–0.7%), respectively. Patients who received a stress test on index visit were less likely to return (adjusted odds ratio [AOR] = 0.64 [95% CI, 0.51–0.80]) but patients who smoked (AOR = 1.51 [95% CI, 1.16–1.96]) or had diabetes (AOR = 1.36 [95% CI, 1.07–1.87]) were more likely to return. Hispanic and African-American patients had increased odds of multiple return ED visits (AOR=1.23 [95% CI, 1.04–1.46] and AOR =1.74 [95% CI, 1.45–2.13], respectively). Conclusion: Patients treated in an ED CPU have a very low rate of MACE at 1 year. However, these same patients have very high rates of subsequent ED utilization. The associations between certain comparative demographics and ED utilization suggest the need for further research to identify and address the needs of these patient populations that precipitate the higher than expected return rate.